Policies to help the working class in the aftermath of COVID-19: Lessons from the Great Recession - Richard V. Burkhauser; Kevin C. Corinth; Douglas Holtz-Eakin (American Enterprise Institute (AEI), 2021)
The COVID-19 pandemic and the associated government mandated shutdowns caused a historic shock to the U.S. economy and a disproportionate job loss concentrated among the working class. While an unprecedented social safety net policy response successfully offset earnings loses among lower-wage workers, the risk of continued and persistent unemployment remains higher among the working class. The key lesson from the Great Recession is that strong economic growth and a hot labor market do more to improve the economic wellbeing of the working class and historically disadvantaged groups than a slow recovery that relies on safety net policies to help replace lost earnings. Thus, the best way to prevent a "K-shaped" recovery is to ensure that safety net policies do not interfere with a return to the strong pre-pandemic economy once the health risk subsides, and that pro-growth policies that incentivize business investment and hiring are maintained.
Keywords: 330; COVID-19 Recession; Great Recession; income growth; employment; safety-net policy; working class